Reconstruction of contact metamorphism of the Uitkomst Complex, near Badplaas, Mpumalanga Province, South Africa, based on mineralogical and petrological investigations of the contact aureole - Kirste, Jens (University of the Free State, 2009)
This study presents petrological, mineralogical and geochemical data from the country rocks surrounding the basic to ultrabasic Uitkomst Complex in the Mpumalanga Province, South Africa. The investigations resulted in a isograde map based on the determination of critical mineral reactions for different lithotypes, i.e. the Timeball Hill Shale, Bevets Conglomerate and the Malmani Dolomite. Several minerals occurring in the metamorphic aureole, for example almandine in the Timeball Hill Shales, allow to determine temperatures and to a lesser degree pressure prevailing in the country rocks during the emplacement of the Complex. Geochemical profiles perpendicular to the contact into the country rocks indicate moderate enrichment of Mg, Fe, Cr and Ni close to the contact, levelling out to threshold values within 50 m distance from the contact. Additionally to the thermometric aspects of this thesis, an appraisal of the possible applications of corundum is given. The Uitkomst corundum shows, in parts, gem quality. Sapphire has been found in the Timeball Hill Shales south of the Complex. The corundum-bearing hornfelses are found in a distance of approximately 240 – 270 m from the contact in north-easterly and south-westerly direction. The rocks in this zone are characterized by a under-saturation of SiO2 and an elevated Al2O3-activity; the required temperature of corundum formation lies above 400 °C on average.
Dissertation (M.Sc. (Geology))--University of the Free State, 2009
Keywords: Petrology -- South Africa -- Mpumalanga; Geochemistry -- South Africa -- Mpumalanga; Mineralogy -- South Africa -- Mpumalanga